Human Resource Development Strategy in Muhammadiyah Charity Enterprises Through IT Training by IMM in Baubau City - Basri; Muhamad Ridwan (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
This study discusses the strategy for developing human resources (HR) in Muhammadiyah Charity (AUM) through information technology (IT) training organized by the Muhammadiyah Student Association (IMM) in Baubau City. In the increasingly developing digital era, mastery of technology is a mandatory competency for workers, including AUM employees. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the IT training provided by IMM has a positive impact on improving the competence of AUM employees, especially in managing digital-based administration, using office software. However, there are several challenges in implementing the training, such as the digital gap between generations, limited IT infrastructure, and lack of post-training assistance. Therefore, a sustainability strategy is needed, such as mentoring, improving digital infrastructure, and organizing more specific advanced training to ensure the effectiveness of this program in the long term. By implementing the right strategy, AUM can be better prepared to face the challenges of digitalization and increase competitiveness in providing more efficient and professional technology-based services.